Association of urate-lowering therapies with abdominal aortic aneurysm growth and clinical events in men: A population-based cohort study - Katja Bøhling Dybdahl; Mathilde Bernal; Marie Dahl; Lasse M. Obel; Jes Sanddal Lindholt; Joachim S. Skovbo (PLoS ONE, 2026)
Objective Abdominal aortic aneurysms (AAA) are potentially life-threatening if they rupture. Xanthine oxidase inhibitors have been suggested to reduce aneurysm growth via urate-lowering and antioxidative mechanisms, though their clinical efficacy remains uncertain. The primary objective of this prospective cohort study was to estimate potential associations between urate-lowering therapies and AAA growth, and secondarily risk of rupture, surgery, all-cause mortality, and major adverse cardiovascular events (MACE), in men aged 65–74. Design This population-based cohort study included data from two large cardiovascular screening trials. Methods The two Danish AAA male cohorts contributed with baseline characteristics, including AAA measurements through ultrasound and computed tomography scans. Participants were followed for five years through linkage with the Danish national health registries. Prescription records defined the exposure of urate-lowering therapies, and participants were categorised as users or non-users. Growth rate was examined using multivariate linear regression, and the secondary outcomes were evaluated using Cox regression. Results This study included 998 men, of whom 73 (7.3%) were exposed to urate-lowering therapies, with a mean defined daily dose of 0.377 per day. During 3 993 person-years, an insignificant mean difference of 0.28 mm/year (95%CI: −0.96–1.52, p = .66) in AAA growth was observed between users and non-users. No associations between urate-lowering therapies and risk of surgery, rupture, all-cause mortality, or MACE were observed. Conclusion The use of urate-lowering therapies was not associated with a reduction in AAA progression. These findings do not support a clinically meaningful effect of urate-lowering therapies on aneurysm progression in men with AAA.